Strengthening Students' Islamic Character Education at SMK Jamiyyatul Aulad Palabuhanratu by Cultivating Morals, Ethics and Culture - U Abdullah Mu'min; Malihah Al Azizah; Budi Munawar Khutomi; Mahamadaree Waeno (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
Islamic character education plays a crucial role in shaping the noble morals and personality of students, particularly in vocational schools. The cultivation of moral, ethical, and cultural values based on Islamic teachings is an effective approach to strengthening student character education. This study aims to examine the application of the concept of moral, ethical, and cultural cultivation in reinforcing Islamic character education at SMK Jamiyyatul Aulad. A qualitative approach with an analytical descriptive method was employed, with data collected through observations, interviews, and documentation, and analyzed using thematic analysis. The results of this study indicate that integrating Islamic moral and ethical cultivation into both learning and extracurricular activities enhances students' awareness of the importance of good morals, discipline, responsibility and mutual respect. Islamic culture, reinforced through daily practices such as congregational prayers (salah), dhuha prayers and social activities, further strengthens the implementation of character education at the school. This study concludes that by integrating Islamic values into the curriculum, exemplifying these values through teachers, habituating religious activities, and involving parents and the community, students can internalize and practice Islamic moral, ethical, and cultural values in their daily lives, thereby enhancing their overall well-being.